La riflessione filosofica, poetica e drammaturgica di Nìkos Kazantzàkis (Itinera, 2016)
This essay gives an account of the work by emblematic Greek author Nìkos Kazantzàkis. Through an analysis on his prose, poetry and theatre works, the essay will shed light on some of the most peculiar aspects of his rich literary and intellectual production, which has been often neglected or criticised.